The invisible intellectuals : Female academics in security and international politics - Aminudin, Rabi'ah (Star Media Group, 2020)
Female academics are visibly absent in the discussion of international politics and security. This put Malaysia at a disadvantaged position as women academics have different research interests and perspectives in the discussion of international politics compared with their male counterparts. Female scholars are prone to explore and discuss non-governmental organisations, transnational actors, and international organisations and adopt a more constructivist approach.